Comportamiento agronómico del pasto Brachiaria decumbens, sometido a dos densidades de siembra con cuatro frecuencias de corte - Basantes León, Erick Leonardo (2016)
VIII. SUMMARY The present research work was carried out at the Experimental Farm San Pablo of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7 ½ of the Babahoyo - Montalvo road. The terrain is located at the geographical coordinates of 79 ° 32' South Latitude, and 1 ° 49' West Latitude, with a height of 8 masl. The genetic material used was Brachiaria decumbens grass seeds from the Marangatu Sementes company, certified by Agrocalidad. Two seed densities (3 and 8 kg of seed / ha) were studied with four cutting frequencies (3, 6, 9 and 12 weeks). The experimental design''Parcelas divididas'' was used with two treatments (seed densities); Four sub-treatments (cut-off frequencies / week) and three replicates. The variables studied were subjected to the Duncan Multiple Rank test at 5% probabilities. For the development of the crop, soil analysis, soil preparation, planting, irrigation, weed control, fertilization, phytosanitary control and harvesting were carried out. Plant height, leaf length and width, stem diameter, flowering days, yield of green and dry matter, bromatological analysis and economic analysis were used to evaluate the effects of treatments and sub treatments. The obtained results determined that the Brachiaria decumbens grass showed good agronomic behavior in two planting densities with four cutting frequencies in the Babahoyo area; The average plant height was 1.1 m; The highest leaf length was obtained using 3 kg of seed / ha with cutoff frequency of 9 weeks, while the average leaf width was 1.9 cm; The diameter of the stem was higher using 8 kg of seed / ha with a cut-off frequency of 12 weeks; The average flowering time for treatments and sub treatments was 98 days and the highest yield of green and dry matter, as well as the highest net benefit was presented using 3 kg of seed / ha with cut frequency of 3 weeks with $ 1366,02